Influence of a ternary donor material on the morphology of a P3HT:PCBM blend for organic photovoltaic devices - Machui, Florian; Rathgeber, Silke; Li, Ning; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry, 2012)
A comparison of grazing incidence wide-angle X-ray scattering (GiWAXS) and differential scanning calorimetric measurements (DSC) was used to identify the influence of a dominantly amorphous small band gap polymer material poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene) -alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) on the crystallinity of a semi-crystalline polymer/fullerene composite. In binary blends the low band gap polymer does not influence the crystalline part of P3HT, but does influence the crystallinity of the fullerene. In ternary blends, a significant drop of the PCBM crystallinity is observed with increasing PCPDTBT content. Adding more than 20 wt% PCPDTBT to a P3HT:PCBM blend leads to a dramatic reduction of device efficiency, mainly due to short circuit current density and fill factor losses. This deterioration is attributed to the fact that addition of more than 20 wt% PCPDTBT to the host system strongly reduces crystallinity of the fullerene phase and electron transport in the ternary system. © 2012 The Royal Society of Chemistry.
Keywords: 2; 1; 3-Benzothiadiazole; Binary blends; Crystallinities; Device efficiency; Differential scanning calorimetric measurements; Electron transport; Fill factor; Grazing incidence; Low bandgap polymers; Organic photovoltaic devices; Semi-crystalline polymer; Small band gap polymer; Ternary blends; Wide angle X-ray scattering Engineering controlled terms: Crystalline materials; Energy gap; Fullerenes; Polymer blends Engineering main heading: Polymers